Come on. Discussion sur un nouveau mot qui émerge et qui va révolutionner notre manière de parler de sexe - Bini Adamczak (Glad!)
This text suggests a new term to speak about sexuality that has been missing: circlusion. Circlusion is the action to push something onto something else. This term allows us to imagine a queer reality liberated from heteronormative domination